Food environment research in Sri Lanka: A desk review - Clarke, Rebecca Namara; Sehgal, Mrignyani; Marshall, Quinn; Kumar, Neha (International Food Policy Research Institute, 2024)
Key Findings • Research has documented the availability of modern food retail (e.g. fast-food) in both urban and rural contexts, and its influence especially on adolescents. • Barriers to accessing healthy diets include the high cost of nutritious foods, especially vegetables and animal source foods, the time needed to cook fresh meals, and food safety • Most research to date has utilized cross-sectional designs, with relatively few studies examining associations with diet or health outcomes, or evaluating interventions.